2018
DOI: 10.1163/15685411-00003130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant and animal waste-based compost amendments on the soil food web, soil properties, and yield and quality of fresh market and processing carrot cultivars

Abstract: A substantial knowledge gap exists on how compost source and rate of application affect nematode community-based soil food web structure, soil health, soil physiochemistry, and crop yield and quality in short- and full-season crops. We tested effects of plant (PC)- and animal (AC)-based compost at 1, 1.5 and 2× the standard nitrogen (N) rate on processing carrot ‘Cupar’ and fresh market ‘Sugarsnax 54’ (short-season crop) over 2-3 growing seasons. Low abundance of nematodes and domination of herbivores and bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Omnivore nematodes normally require 95 to 130 days to complete a life cycle (McSorley, 2012). The significant increase in SI from 50 in the nematode faunal profile of the present study suggested that PC alone and U1:PC1 improved soil food web structure with greater trophic links (Ferris et al, 2012;Habteweld et al, 2018). SI values are usually low in agroecosystems because of physical and/or chemical disturbances of the soil (Fiscus and Neher, 2002;Berkelmans et al, 2003;Briar et al, 2011).…”
Section: Effect On Soil Food Web Conditionmentioning
confidence: 67%
See 1 more Smart Citation
“…Omnivore nematodes normally require 95 to 130 days to complete a life cycle (McSorley, 2012). The significant increase in SI from 50 in the nematode faunal profile of the present study suggested that PC alone and U1:PC1 improved soil food web structure with greater trophic links (Ferris et al, 2012;Habteweld et al, 2018). SI values are usually low in agroecosystems because of physical and/or chemical disturbances of the soil (Fiscus and Neher, 2002;Berkelmans et al, 2003;Briar et al, 2011).…”
Section: Effect On Soil Food Web Conditionmentioning
confidence: 67%
“…The plots were separated by 1.83 m wide guard rows between their length and 1.52 m between their widths. PC from leaves of different plant species left to decompose for more than 10 years obtained from MSU Student Organic Farm, Holt, MI, USA, analyzed for nutrient contents, and applied on dry matter basis ( Habteweld et al, 2018 ). The standard urea was obtained from MSU Horticulture Teaching and Research Center in Holt, Michigan.…”
Section: Methodsmentioning
confidence: 99%
“…Fertilization‐induced changes in soil properties and resource availability are considered as two of the major factors regulating responses of soil faunal communities to fertilization (Lemanski & Scheu, 2015; Miller et al, 2017). Fertilization‐induced changes in soil properties, such as soil moisture content, soil pH and essential minerals, can affect the living habitats of soil fauna, hence their communities (Habteweld et al, 2018; Li et al, 2018; Miller et al, 2017). Additionally, the consistent supply of nutrients and food resources directly or indirectly from fertilizers can lead to changes in soil faunal communities (Brandl, 2014; Jiang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the consistent supply of nutrients and food resources directly or indirectly from fertilizers can lead to changes in soil faunal communities (Brandl, 2014; Jiang et al, 2015). Moreover, the application of fertilizers to soil can also support (Habteweld et al, 2018) or suppress (Cao et al, 2011) soil microbes, which changes resource availability for soil fauna, hence their abundance (Aslam et al, 2015; Lemanski & Scheu, 2015; Zhang et al, 2017). Although these individual studies have undoubtedly advanced our understanding of the relationships between fertilization and changes in the soil faunal community, the regulatory factors of fertilization on soil faunal communities remain unclear at the global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Beta vulgaris L. (sugar beet) is the second largest sugar crop globally, whose demand was continuously increased [1]. The growth of Beta vulgaris L. is closely related to the rhizosphere soil microbes with plant roots providing habitats and nutrient sources for soil organisms and driving the interaction between soil organisms and the environment [2]. Rhizosphere soil is enriched with a huge number of living organisms [3], among which the number of microorganisms and protozoa being the largest and their interaction directly affects the physicochemical properties and biochemical processes of rhizosphere soil [4][5][6].…”
Section: Introductionmentioning
confidence: 99%